Notas filosóficas provisionales sobre la esencia del cristianismo - García-Baró, Miguel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
The substance of Christianity lies in the idea — utterly dazzling and disruptive of so many other ideas — that humanity and divinity are united; i. e., that this often diabolical humanity is nevertheless capable of God; and it is so not because of its natural condition but by divine condescension, even though it calls forth the highest energies of the human being. These energies must often be devoted to the destruction of the evil in oneself, to a kind of deconstruction of the figure that is formed as one lives, rather than to the construction of any other. Only innocence, only a seemingly impossible second innocence, a second childhood, is God’s capacity.